2016
DOI: 10.1186/s40795-016-0065-7
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of rice endosperm protein intake in Japanese men with risk factors for metabolic syndrome: a randomized, crossover clinical trial

Abstract: Background: Rice protein is proved to have hypocholesterolemic and anti-atherosclerotic effects, and a few experimental studies showed its renoprotective effects, using animal diabetic models. However, no clinical studies have investigated its benefits for human health. We aimed to clarify how the intake of rice endosperm protein affects markers correlating to lipid dysfunction in human. Methods: We recruited 18 male volunteers, 26-64 years of age, with risk factors for metabolic syndrome and allocated randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Further studies using different animal models may be needed to verify our findings. However, instead of conducting further animal research, it would be preferable to start human trials with REP. REP has been administered safely to human patients undergoing dialysis [53], and it has also shown beneficial effects on metabolic syndrome in adults [54]. Therefore, we suggest that the intake of REP or rice-based diets in childhood may prevent obesity and related disorders in adult humans.…”
Section: Discussionmentioning
confidence: 93%
“…Further studies using different animal models may be needed to verify our findings. However, instead of conducting further animal research, it would be preferable to start human trials with REP. REP has been administered safely to human patients undergoing dialysis [53], and it has also shown beneficial effects on metabolic syndrome in adults [54]. Therefore, we suggest that the intake of REP or rice-based diets in childhood may prevent obesity and related disorders in adult humans.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, a single clinical trial reported that the administration of a daily dose of 10 g of rice endosperm protein for four weeks was able to increase HDL-C levels and reduce serum uric acid levels in adult male subjects with metabolic syndrome risk factors. However, no changes in TGs or LDL-C were observed [132]. Additional clinical trials are needed to evaluate the antioxidative and hypocholesterolemic effects of rice protein.…”
Section: Hypercholesterolemiamentioning
confidence: 98%
“…REP accounting for approximately 5% of rice endosperm is not only nutritionally important but also shows various physiological functions such as anti-hyperglycemia, antihyperuricemia, and anti-obesity when orally administrated [7][8][9]. Recently, there have been various peptides derived from food protein resources reported to exhibit physiological functions [10,11].…”
Section: Introductionmentioning
confidence: 99%